When and Why Java was Deliberated from the Slavery? - Djoko Marihandono (Diponegoro University, 2017)
Java islands as one of the colonies on the European nations in Asia, had several changes since the Dutch Government liquidated the operation. This condition was caused by the change of the political constellation in Europe since the end of this century. As we knew that since 1795 till 1813, the Netherland was dominated by the French. From the year 1795, in January, the Bataafsche Republic was established in Netherland, supported by French after the governor (Staathouder) escaped by leaving his country to London. The result of this fact, the changes were happened in all provinces in Netherland and in almost of its colonies, included in Java. The form of the government was changed because of the implementation of the French Revolutionary ideas. How to overlook the colonies were different compared by the VOC era. In VOC era, East India had been looked as the economical point of view. In the other hand, in Bataafsche Republic era, it had been considered as the integrated territory of French. So, there was a different management of both. During the VOC era, East India was placed under the Ministry of trade and colony regions. Then, in the Bataafsche Republic era, it was located under the Ministry of Maritime Army and the Colonies.The status of this colony was totally changed. The consequence of this change, there were a reformation of the social, politic and economic. The influences of the liberation idea, the main idea of French Revolution, was applied in almost all the regulations of its colony regions. Human rights guaranteed the rights not only as individual but also as a member of society. The Governor General deliberated all slaves in Java and others several islands to be trained as the soldiers.From the French point of view, Java would be set as centre of the French strategy in the effort to reoccupy India as before. According to Napoleon Bonaparte, India had natural resources more than the riches of all European kingdoms. So, the position of Java island geographically was very important because of his location was directly in front of India Ocean, and the military troupes could directly attack India. Java which was very rich of the natural resources as wood as the basic materials of ship industry, potassium nitrate, as the materials of ammunition and the Javanese who had the very special endurance were considered by the Emperor as a very ideal island. The Javanese could compete the Sepoy soldiers, the Indian indigenous soldiers formed by the British. So, Napoleon Bonaparte considered that the Javanese would be prepared to realize the Napoleonic strategy. Java had to be saved from the British attack.